AN IMPACT ANALYSIS OF ACQUISITIONS ON FINANCIAL PERFORMANCE AT PT SUMBER ALFARIA TRIJAYA TBK (AMRT) FOR THE 2016-2022 PERIOD - Muhammad Raihan Rafli (Journal of Management and Islamic Finance, 2024)
In 2019, PT Sumber Alfaria Trijaya Tbk (AMRT), which is the holding company of Alfamart, acquired 75% of GLI shares with the aim of increasing cooperation between the company's shopping applications and promotional programs with membership programs that were developed by GLI. This study is to analyze the financial performance of PT Sumber Alfaria Trijaya Tbk 3 years before and 3 years after the acquisition with PT Global Loyalty Indonesia. This research adopts a comparative quantitative method and is analyzed using descriptive statistics. Financial performance is measured using 7 financial ratios including CR, TATO, NPM, ROA, ROE, EPS and DER. The results showed that the company's liquidity and solvency decreased, and the company's profitability increased.